Million dollar consulting proposals how to write a proposal that is accepted every time - Weiss, Alan, 1946-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"Bestselling author of Million Dollar Consulting shares the secrets of writing winning proposalsIntended for consultants, speakers, and other professional services providers, Million Dollar Consulting Proposals ends forever the time-consuming and often frustrating process of writing a consulting proposal. It begins with the basics--defining these proposals and why they are necessary--and coaches you through the entire proposal process. In this book, you'll learn how to establish outcome-based business objectives and maximize your success and commensurate fees.From bestselling author Alan Weiss, Million Dollar Consulting Proposals delivers step-by-step guidance on the essential element in creating a million dollar consultancy. Outlines the nine key components to a Million Dollar Consulting proposal structure Presents a dozen Golden Rules for presenting proposals Offers online samples, forms, and templates to maximize the effectiveness of these tools The New York Post calls bestselling author Alan Weiss "one of the most highly regarded independent consultants in America." Alan Weiss's expert guidance can lead your consulting business to unprecedented success, and it all starts with a million dollar proposal"--
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business consultants; Consulting firms -- Management; Consultants -- Marketing; Electronic books